Implementation of Hospital Internal Audit Policy - Sudalhar, Sudalhar; Handoko, Rudy; Maduwinarti, Ayun (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Out of 7 people in the Internal Audit Unit (SPI) in a hospital, only 1 person is not concurrently serving as the Head of SPI. SPI is the main requirement in carrying out duties and can be a problem in the implementation of hospital internal audit policies by SPI and if this is left unchecked, the public services provided by the hospital can be of less quality. the purpose of this study is to know and analyze the implementation of internal audit policies, factors that support and hinder the implementation of internal audit, find models for implementing internal audit policies in Hospital A. Subjects and Method: qualitative research design. The research was conducted at Aisyiyah Bojonegoro Hospital. The target population consists of 1 director, 6 department heads and 4 SPI auditors. The technique and size of sampling is done by means of the population being the sample. the dependent and independent variables of interest are the implementation of the Hospital Internal Audit policy. Variable measurement methods or instruments by means of interviews and data analysis methods using data triangulation. Results: The implementation of internal audit policy from the communication aspect has been carried out well, the Resource aspect has not been implemented properly, the Disposition aspect has not been implemented properly, the Organizational Structure aspect is carried out properly. The appointment of SPI personnel needs to take into account the competence of the auditor or provide auditor competency training, exemption from concurrent duties and full-time positions, structuring systematic career paths and providing special incentives, maintaining consistency of communication and conducting audits in all work units Conclusion: This research can produce implications for model development in the implementation of hospital internal audit policies in accordance with Edward III's theory and then developed with the involvement of the Hospital Internal Auditors Association. Through this it is expected that the implementation of internal audit policies is more comprehensive in implementing aspects of organizational structure, resources, disposition and communication. Keywords: implementation, policy, internal audit, hospital Correspondence: Sudalhar. University of 17 August 1945 Surabaya, Semolowaru Street Number 45, Menur Pumpungan, Sukolilo District, Surabaya, East Java 60118. Email: dalharaljafar@gmail.com. Mobile: 08125928651